An Analysis on the Influence of Digital Marketing, Entrepreneurial Networking, on Msme Business Performance with the Use of Payment Sistem Quick Response Indonesia Standard (Qris) As Moderating Variable In Medan - Masria Lumban Gaol; Eni Duwita Sigalingging (Enrichment : Journal of Management, 2022)
The objective of the research was to find out 1) the influence of Digital Marketing, Entrepreneurial Networking on MSME Business Perfomance in Medan, and 2) The using QRIS payment sistem in modernizing the influence of Entrepreneurial Networking, Competitive Advantage on MSME Business Perfomance in Medan, The population used causality method. The population was 100 MSME in Medan Amplas, and all of them were used as the samples and analyzed by using measurement model (outer model) and structural model (inner model), and effect size for moderating variable. The result of the research showed that 1) Digital Marketing, Entrepreneurial Networking had positive and significant influence on MSME Business Perfomance in Medan, and 2) The using QRIS payment sistem could moderate the influence of Digital Marketing, Entrepreneurial Networking on MSME Business Perfomance in Medan.